ANALISIS SGPT-SGOT EKSTRAK ETANOL DAGING BUAH PARE (Momordica charantia L.) PADA TIKUS JANTAN PUTIH GALUR WISTAR - Dwi Ari Nugrahani; Vivi Sofia (Universitas Ahmad Dahlan, 2011)
The traditional medicine in Indonesia which is the cultural heritage and hasbecome an integral part of the life of the nation Indonesia, want to be employed in theformal health care system. As the circulation of drugs in general terms, traditionalmedicine should fulfill the requirements of quality, safe, and efficacious. This studyaims to analyze the levels of SGPT, SGOT of suspension of the ethanol extract of bittermelon fruit (Momordica charantia L.) by orally. The study was conducted using a whitemale Wistar rats amounted to 36 animals, divided into 6 groups. Each group consistedof 6 male white rats. Group I (control) were given 0.5% CMC solution of 2.5 ml/200 gBW. Group II was given a suspension dosage doses of bitter melon fruit extract ethanol0.5 g/kg, then consecutive group III with the test preparation doses of 1 g/kg, the testpreparation group IV were given a dose of 2 g/kg, group V was given dosage test doseof 4 g/kg, and group VI were given the highest dose of the test preparation 8 g/kg. Theresults of acute toxicity tests on white male Wistar rats showed that administration ofethanol extract of peroral dosage suspension pare (Momordica charantia L.) singledose on white male Wistar rats from the dose of 0.5 g/kg until a dose of 8 g/kg did notsignificantly influence the value of SGPT, SGOT.